Supporting pro-environmental behavior change with a carbon calculator - The design of user challenges - SO, MARTIN; ZHOU, MENGWEI (My University, 2020)
The purpose of this thesis was to research important factors to consider when designing user challenge in carbon calculators to support behavior change in the users towards a sustainable lifestyle. Therefore, a design in this context was created in order to research and extract important factors for designing the challenges. In order to create the design and extract the design factors from it, an iterative design process was conducted. This involved researching theory in the field of study, researching users of carbon calculators, designing solutions, evaluating the solutions with users of carbon calculators, and finally, extracting design factors based on analyzing all findings throughout the process. In the end, this resulted in a design created and important factors to consider when designing challenges in carbon calculators. The design can act as a visual design reference or inspiration for designing challenges in carbon calculators. But more importantly are the design factors, which could be used by others who conduct work in this context.
Keywords: Carbon calculator; pro-environmental behavior change; pro-environmental challenges; interaction design; persuasive technology; sustainability; Svalna